Utility of MAG3 scintigraphy with the use of a 2 min uptake parameter in the assessment of postsurgical renal transplant complications. Issue 10 (October 2018) - Lee, Su-Faye; Lichtenstein, Meir; Hughes, Peter; Sivaratnam, Dinesh
Abstract : Objective: Major complications including acute tubular necrosis or rejection may occur after renal transplantation. We use a semiquantitative parameter, 2 min uptake (2MU), as part of 99m Tc mercaptoacetyltriglycine (MAG3) scintigraphy for transplant evaluation. The aim of this study were (a) to examine the utility of 99m Tc MAG3 scintigraphy in the assessment of postsurgical complications using the renal biopsy as the gold standard and (b) examine for any correlation with 2MU with serum creatinine (sCr) at 3 and 12 months. Materials and methods: We retrospectively reviewed all 99m Tc MAG3 studies at our institution between July 2015 and June 2016, alongside available renal ultrasound, biopsy, and sCr results. Results: A total of 105 patients fulfilled the inclusion criteria. 30/105 patients underwent biopsy less than 7 days of the 99m Tc MAG3 study. Within this 7 day cohort, the negative predictive value for rejection with normal perfusion on 99m Tc MAG3 study was 79% and the positive predictive value for rejection with abnormal 99m Tc MAG3 perfusion was 9%. There was a weak negative correlation between 2MU and 3-month sCr ( R =−0.358, P <0.001), and 2MU and 12-month sCr ( R =−0.348, P <0.001). Conclusion: Although normal perfusion on 99m Tc MAG3 scintigraphy study has a reasonable negative predictive value for rejection, abnormal 99m Tc MAG3 perfusion is not useful in the differentiation of rejection from moderate to severe acute tubular necrosis. The 2MU parameter showed no additional benefit in the identification of rejection, but appeared to have a weak negative correlation with the 3-month and 12-month sCr, and may thus play a role in the prediction of longer term graft function.